Characterising the asynchronous resurgence of common respiratory viruses following the COVID-19 pandemic - Chenkai Zhao; Tiantian Zhang; Ling Guo; Shiqi Sun; Yumeng Miao; Chee Fu Yung; Jane Tomlinson; Kirill Stolyarov; Zakhar Shchomak; Yong Poovorawan; David James Nokes; Carmen Muñoz-Almagro; et al. (Nature Communications)
Abstract The COVID-19 pandemic and relevant non-pharmaceutical interventions (NPIs) interrupted the circulation of common respiratory viruses. These viruses demonstrated an unprecedented asynchronous resurgence as NPIs were relaxed. We compiled a global dataset from a systematic review, online surveillance reports and unpublished data from Respiratory Virus Global Epidemiology Network, encompassing 92 sites. We compared the resurgence timings of respiratory viruses within each site and synthesised differences in timings across sites, using a generalised linear mixed-effects model. We revealed a distinct sequential timing in the first post-pandemic resurgence: rhinovirus resurged the earliest, followed by seasonal coronavirus, parainfluenza virus, respiratory syncytial virus, adenovirus, metapneumovirus and influenza A virus, with influenza B virus exhibiting the latest resurgence. Similar sequential timing was observed in the second resurgence except influenza A virus caught up with metapneumovirus. The consistent asynchrony across geographical regions suggests that virus-specific characteristics, rather than location-specific factors, determining the relative timing of resurgence.